Tracing Islamic Moderatism in Tafsir An-Nur: A Study of Hasbi Ash-Shiddieqy's Thought and Its Relevance to Religious Moderation in Indonesia: Jejak Moderatisme Islam dalam Tafsir An-Nur: Studi Pemikiran Hasbi Ash-Shiddieqy Serta Relevansinya bagi Moderasi Keagamaan di Indonesia (Takwil: Journal of Quran and Hadith Studies, 2026)
This study aims to reconstruct the concept of religious moderation in Tafsir An-Nur by Hasbi Ash-Shiddieqy and examine its relevance within the Indonesian context. This research employs a qualitative approach using library research, focusing on a thematic (maudhu'i) analysis of Qur'anic verses that embody the values of religious moderation, including Qur'an 2:143, 2:43, 2:183, 4:3, and 2:282. The primary source of data is Tafsir An-Nur, while secondary data are drawn from various works on Qur'anic exegesis and studies of religious moderation. The data were analyzed through thematic identification, concept coding, interpretation, and synthesis. The findings reveal that Hasbi Ash-Shiddieqy constructs the concept of religious moderation through the principles of tawassuth (the middle path), tawazun (balance), and i'tidal (justice). The value of tawassuth is reflected in maintaining equilibrium between worldly and spiritual affairs while rejecting extremist attitudes. The principle of tawazun is manifested in the integration of spiritual and social dimensions, such as the interrelationship between prayer and zakat, as well as the balance between physical and spiritual well-being during fasting. Meanwhile, i'tidal is demonstrated through the emphasis on justice in family relationships and economic transactions. Hasbi's interpretation is contextual, rational, and practical, making it highly relevant to Indonesia's pluralistic society. Therefore, Tafsir An-Nur provides a valuable conceptual foundation for strengthening religious moderation in order to promote social harmony, prevent radicalism, and foster an inclusive and civilized religious life.